A Tailing Dump as Industrial Deposit; Study of the Mineralogical Composition of Tailing Dump of the Southern Urals and the Possibility of Tailings Re-Development - Elena N. Shaforostova; Olga V. Kosareva-Volod’ko; Olga V. Belyankina; Danila Y. Solovykh; Ekaterina S. Sazankova; Elena I. Sizova; Danila A. Adigamov (Resources, 2023)
It is found that regions with depleted, or on the verge of depletion, of mineral resources are subject to additional pressures due to intensifying social and environmental problems. This paper proposes the development of the mining industry, reducing the dependence of the economy on the sharp volatility of the raw materials market in a period of global shocks by addressing social and environmental problems in regions with a depleting mineral resource base. It is assumed that the geotechnology development from simple mineral extraction to technologies providing a full cycle of georesources development with industrial waste recycling contributes to the resource provision of sustainable development. The material and mineralogical composition of the four tailing dumps (Uchalinskiy, Buribayskiy, Sibayskiy and Gaiskiy Ore-Processing plants have been studied) united with the similarity of the processed raw materials, and as a consequence, the similar enrichment technology has been studied and established. An approximate estimate of valuable components left in industrial wastes was made. The possibility of valuable component extraction (e.g., gold) from tailings using double agitation cyanidation was substantiated. There is no necessity of obligatory grinding of tailings to increase the recovery rate of valuable components. It was experimentally determined that the extraction of gold from tailings is 75.9–82.14% and depends on the investigated technogenic raw material. It has been proved that industrial waste can be recycled for the purpose of the resource provision of sustainable development. The need for further, more detailed studies of industrial formations has been identified. This will help to identify patterns of valuable component distribution in the industrial mass and to study its extraction possibilities in more details.